CIPP Evaluation Model: Analysis of Education Implementation in PAUD Based on Government Policy on Implementation of Learning During the Covid-19 Pandemic - Dadan Suryana; Amalia Husna; Nenny Mahyuddin (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
During the Covid-19 pandemic, various policies related to learning implementation procedures were launched by the government at various levels of education, including the PAUD level. This policy aims to prevent the transmission of Covid-19 and the continuity of education during the pandemic. This study aims to analyze the implementation of education in PAUD based on government circulars/policies regarding the application of learning during the pandemic through the CIPP evaluation model. This research is qualitative research with the CIPP evaluation model method. The evaluation of the CIPP model has four interrelated components, namely the evaluation of Context, Input, Process and Product (CIPP). The subject of this research is PAUD-KB Nurfajrin. The research results on the context aspect, the application of learning during the pandemic was due to individuals having to keep their distance to prevent transmission. In the input aspect, the implementation of learning is by government policy. Teachers and parents receive assistance from the government for the fulfilment of facilities and infrastructure. Therefore, teachers and parents can work well together, and children are well prepared. In the process aspect, learning during the Covid-19 pandemic went well. Lastly, on the product aspect, during the learning process during the pandemic, there were no students, parents or teachers who were positive for Covid-19. In addition, during learning during the pandemic, children also experienced good development.